Development of a classification system for Philippine local studies materials - Jimenez, Mary Ann Q. (2006)
This study sought to investigate the extent of collection and methods of organization of selected local studies centers in Luzon as basis for a proposed development of a classification system for local studies materials. Survey questionnaires, actual visits and interviews were used to gather data. Likewise, surveys of published and unpublished local studies materials at UP Main Library, UST Central Library and National Library were conducted to get samples of types of materials which may be classified with the proposed scheme.